2022
DOI: 10.2166/wst.2022.038
|View full text |Cite
|
Sign up to set email alerts
|

Towards the long term implementation of real time control of combined sewer systems: a review of performance and influencing factors

Abstract: Real Time Control (RTC) is widely accepted as a cost-effective way to operate urban drainage systems (UDS) effectively. However, what factors influence RTC efficacy and how this might change in the long term remains largely unknown. This paper reviews the literature to understand what these factors likely are, and how they can be assessed in the future. Despite decades of research, inconsistent definitions of the performance of RTC are used, hindering an objective and quantitative examination of the benefits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 144 publications
(182 reference statements)
0
16
2
Order By: Relevance
“…Real Time Control (RTC) is an emerging water management strategy (Garrido-Baserba et al, 2020;Voutchkov, 2019), that aims at using data collected in real time to adjust the operation of the system (in this case, the CS network) pursuant a goal, that in our case is the reduction of CSOs. Van Der Werf et al (2022) review RTC applications for CSO management by referring to a set of case studies (see Appendix 3). By plotting the CSO volume reduction in the case studies as a function of the initial CSO volume, we found that the reduction of CSO annual volumes could be expressed as a function of the current CSO volumes, by means of a power law equation (further described in Appendix 3) with R 2 = 0.87 and mean absolute error of 36%.…”
Section: ) Real Time Controlmentioning
confidence: 99%
See 3 more Smart Citations
“…Real Time Control (RTC) is an emerging water management strategy (Garrido-Baserba et al, 2020;Voutchkov, 2019), that aims at using data collected in real time to adjust the operation of the system (in this case, the CS network) pursuant a goal, that in our case is the reduction of CSOs. Van Der Werf et al (2022) review RTC applications for CSO management by referring to a set of case studies (see Appendix 3). By plotting the CSO volume reduction in the case studies as a function of the initial CSO volume, we found that the reduction of CSO annual volumes could be expressed as a function of the current CSO volumes, by means of a power law equation (further described in Appendix 3) with R 2 = 0.87 and mean absolute error of 36%.…”
Section: ) Real Time Controlmentioning
confidence: 99%
“…Real time control can help in CSO mitigation (Colas et al, 2004;Van Der Werf et al, 2022), and it can be classified into local control systems, or system-wide control systems, where the former type is less expensive but with less relevant efficacy at the large scale (e.g. the whole city scale) (Eulogi et al, 2022).…”
Section: Appendixmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, most studies seeking the optimal strategies in controlling a sanitation system are focusing on reducing overflow volume. 48 Few studies can be found to optimally reduce the overflow mass loading, which is correlated with the overflow volume through the concentration of sewer flow and directly impacts the water quality of receiving waters. While the control of overflow volume employs hydraulic models, both hydraulic and water quality models are factored into the control of overflow mass.…”
Section: Insights Into the Distributed Optimal Regulationmentioning
confidence: 99%